Astrocytic activation in the anterior cingulate cortex is critical for sleep disorder under neuropathic pain. Issue 6 (24th February 2014) - Yamashita, Akira; Hamada, Asami; Suhara, Yuki; Kawabe, Rui; Yanase, Makoto; Kuzumaki, Naoko; Narita, Michiko; Matsui, Ryosuke; Okano, Hideyuki; Narita, Minoru
ABSTRACT Insomnia, depression, and anxiety disorder are common problems for people with neuropathic pain. In this study, mild noxious heat stimuli increased the duration and number of spontaneous pain‐like behaviors in sciatic nerve‐ligated mice. We used functional magnetic resonance imaging to visualize the increased blood oxygenation level‐dependent signal intensity in the anterior cingulate cortex (ACC) of mice with sciatic nerve ligation under mild noxious stimuli. Such stimuli significantly increased the release of glutamate in the ACC of nerve‐ligated mice. In addition, sciatic nerve ligation and mild noxious stimuli changed the morphology of astrocytes in the ACC. Treatment of cortical astrocytes with glutamate caused astrocytic activation, as detected by a stellate morphology. Furthermore, glutamate induced the translocation of GAT‐3 to astrocyte cell membranes using primary cultured glial cells from the mouse cortex. Moreover, the GABA level at the synaptic cleft in the ACC of nerve‐ligated mice was significantly decreased exposure to mild noxious stimuli. Finally, we investigated whether astrocytic activation in the ACC could directly mediate sleep disorder. With the optogenetic tool channel rhodopsin‐2 (ChR2), we demonstrated that selective photostimulation of these astrocytes in vivo triggered sleep disturbance. Taken together, these results suggest that neuropathic pain‐like stimuli activated astrocytes in the ACC and decreased the extracellular concentration of GABA via an increase in the release of glutamate. Furthermore, these findings provide novel evidence that astrocytic activation in the ACC can mimic sleep disturbance in mice. Synapse 68:235–247, 2014. © 2014 Wiley Periodicals, Inc.